PERAN ISTRI NELAYAN DALAM MENUNJANG KEHIDUPAN KELUARGA DI KELURAHAN BUNGKUTOKO KECAMATAN NAMBO KOTA KENDARI - Sukmawati Abdullah (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
This study aims to determine the role of fishermen's wives in supporting family life in Bungkutoko Village, Nambo District, Kendari City. The population in this study consisted of all wives of capture fishermen in Bungkutoko Village, totalling 460 people. The sample was determined using the Slovin formula with an error rate of 10%, resulting in a population of 82 respondents. This research employs a quantitative approach. Data were collected through interviews and document analysis, employing a quantitative descriptive approach using the class interval formula. The results indicated that the role of fishermen's wives in supporting family life can be broadly classified into two sectors: the domestic and the public. The domestic sector encompasses a moderate role, as evidenced by the ability of nalayan women to fulfill their responsibilities to their husbands and children. Although the role of fisherwives in the sector is relatively limited due to the small number of fisherwives engaged in earning activities, it is evident that fisherwives play an important role in supporting the economy and meeting the needs of fishermen and their families.